PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH - Mutmainnah Mutmainnah (Jurnal Manajemen dan Pemasaran Jasa, 2017)
As a primary factor in satisfaction and loyalty, service quality and image has been given a lot of attention. This research used a sample of 120 respondents and analyzed the data using structural equation modeling. Findings reveal that service quality and corporate image are antecedents of customer satisfaction, but customer satisfaction surprisingly does not have positive and significant effect on customer loyalty. The implications for service providers in any platform service industry is that customer satisfaction has not key success to loyalty but continuously improves the quality of service and corporate image of satisfaction, but it creates loyalty to buy services and recommend to others.